3 Neonatal airway training (NAT) course: technical skills and teamwork for neonatal emergencies. (22nd November 2019) - Jinks, Stephanie; Miskovic, Alice
Abstract : Neonatal airway management is universally challenging across specialities. Paediatricians have minimal formal airway training built into their curriculum, and anaesthetists have limited exposure to neonates. Great Ormond Street routinely managed complex neonatal patients and the multidisciplinary team includes experts in paediatric anaesthesia, neonatology, ENT surgery and tracheostomy management. We therefore developed a one-day cross-speciality course delivering basic and advanced neonatal airway training aimed at speciality registrars and consultants working within the London area. The course consists of lectures (anatomy, physiology, pharmacology and 'the difficult airway'), preceding small group rotations through 3 core skills stations; bag mask ventilation, supraglottic airways and intubation and 3 advanced skills; tracheostomies, videolaryngoscopes and difficult airway algorithm. Finally candidates, in role, manage high fidelity simulated emergencies within teams on the neonatal unit, delivery suite and emergency department focusing on human factors and skills learnt. The course is approved for 6 CPD points from both Royal colleges. Questionnaires using a 5-point likeart scale from 1 to 5 (not at all to very confident) assessed post course improvement in skills, ability to manage unwell neonates and improvement in team working. All candidates improved globally and enjoyed the cross-speciality team approach. Mean skill scores increased by at least 1 point with greatest improvement in advanced skills. Paediatricians in particular felt the course was so valuable that it should be compulsory for all ST3 trainees. The NAT course was designed to improve airway skills but feedback from faculty and delegates demonstrates that learning encompasses many areas. They include greater understanding and confidence with equipment, improved basic and advanced clinical skills and the teamwork and situational awareness required to manage neonatal emergencies. We are embarking on our second course in November and the course is already established in Leeds with hospitals in Southampton and Vancouver soon to follow our lead.